FINANCIAL PERFORMANCE OF BANKS IN INDIA - Pokale, Amitkumar Prakashrao; Shetiya, Mahavir Manikchand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The financial performance of banks in India is a crucial indicator of their ability to generate profits and remain sustainable in the long run. This research paper aims to analyze the financial performance of banks in India using various financial ratios such as profitability, liquidity, and asset quality ratios. The study utilizes secondary data from the financial statements of selected banks in India for the period 2016-2020. The findings of the study reveal that profitability ratios are the most significant indicators of financial performance, followed by liquidity and asset quality ratios. The paper concludes that banks in India must focus on maintaining a healthy balance between profitability, liquidity, and asset quality to ensure long-term sustainability.